High-level South Korean Athletes` experiences of injury and rehabilitation - Bejar, M. P.; Fisher, L. A.; Nam, B. H.; Larsen, L. K.; Fynes, J. M.; Zakrajsek, R. A. (The Sport Psychologist, 2017)
Although the biopsychosocial model of sport injury rehabilitation (Brewer, Andersen, & Van Raalte, 2002) is one of the most comprehensive frameworks to address athletes` post-injury responses, there has been little research centralizing the myriad of cultural factors (e.g., nationality, ethnicity, socioeconomic status) that can impact psychological, social/contextual, and biological factors that, in turn, impact athletes` recovery. The purpose of the current study was to explore high-level South Korean athletes` experiences of injury and rehabilitation. Retrospective semi-structured interviews were conducted with 11 retired high-level South Korean athletes. Employing Consensual Qualitative Research (CQR) methodology (Hill, 2012), four domains were constructed from the data: (a) Experience of the South Korean Sport System, (b) Immediate Post-Injury Perceptions, (c) Experience of Recovery Process, and (d) Post-Injury Reflections. The findings indicated that participants` experiences of the forced hierarchy and power dynamics within the South Korean athletic specialist system influenced perceived sport injury rehabilitation outcomes.